STUDY THE EFFECT OF ADDING CUSO4 ON THE STRUCTURAL PROPERTIES AND MECHANICAL SPECIFICATIONS OF LOW DENSITY POLYETHYLENE (ResearchJet Journal of Analysis and Inventions, 2022)
Polymer composite materials were manufactured The base material was made of low-density polyethylene using the thermal fusion method and supported using CuSO4 powder, which is in the Nano-form and in volumetric ratios by adding (5,10,15,20,25), the manufactured models were thermally treated for three periods (3,6,9) and at temperatures (40,60,80). The models were subjected to a set of mechanical tests that include (shear stress, compressive strength), X-ray diffraction (XRD) and scanning electron microscopy (SEM) examinations. Mechanical properties, where a state of filling the voids occurs regularly and effectively, and this percentage was within the 15%, in addition to the temperature, which played a major role in improving some of the polymeric properties shown by the mechanical properties of the manufactured composite material.